Proceedings of the Seminar on World Forum for Harmonization of Vehicle Regulations, 14 May 2002, Auditorium SIRIM Berhad, Shah Alam, Selangor - Seminar World Forum for Harmonization of Vehicle Regulations (2002 : Shah Alam, Selangor) ([S.l. : s.n.], 2002)
20